ANALISIS VALUE CHAIN DAN EFISIENSI PEMASARAN AGRIBISNIS JAMUR KUPING DI KABUPATEN KARANGANYAR - HERU IRIANTO; EMY WIDIYANTI (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2013)
The objective of research is to study the value chain and efficiency of jamur kuping (wood ear or cloud ear mushroom) agribusiness in Karanganyar Regency of Central Java. The data collection was conducted with interview technique, using questionnaire prepared previously. Meanwhile the sample was taken using non-probabilistic technique with seeder as the entry point that was investigated using snowball system to obtain the sample from the next point to the consumer. From this technique, 47 samples were obtained consisting: 2 seeders (the one who cultivate the seed), 12 bagloger, 21 farmers, 12 traders with varied level.